2011
DOI: 10.1007/s10658-011-9864-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of genes involved in the biotrophic colonisation of Coffea arabica leaves by Hemileia vastatrix

Abstract: Coffee Leaf Rust, caused by Hemileia vastatrix, is the most important disease of Arabica coffee (Coffea arabica), which prompts studies aimed at understanding the genetic basis of this pathogen as well as its complex interaction with the host. In this work, 11 genes, putatively involved in signalling, establishment and maintenance of biotrophy (transport and metabolism), were characterised, and their expression profiles during host infection were assessed by RT-qPCR in three compatible coffee-rust interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…A third level of response, suggested by haustoria-induced cell death in the host interaction, could not be traced at the molecular level, presumably because of the low level of infection sites where haustoria were formed. Interestingly, a similar biphasic activation of fungal genes involved in signalling and pathogenesis was reported at similar differentiation stages of H. vastatrix during colonisation in compatible interactions with C. arabica (Vieira et al 2011).…”
Section: Fig 4 Percentage Of Infection Sites With Infection Structursupporting
confidence: 68%
“…A third level of response, suggested by haustoria-induced cell death in the host interaction, could not be traced at the molecular level, presumably because of the low level of infection sites where haustoria were formed. Interestingly, a similar biphasic activation of fungal genes involved in signalling and pathogenesis was reported at similar differentiation stages of H. vastatrix during colonisation in compatible interactions with C. arabica (Vieira et al 2011).…”
Section: Fig 4 Percentage Of Infection Sites With Infection Structursupporting
confidence: 68%
“…The genomes of Pgt and Mlp [23] as well as the secretome of the symbiont Laccaria bicolor [56], were also found to be enriched in chitin deacetylase genes. Expression profiling of the biotrophic stage of the coffee rust Hemileia vastatrix suggested that two chitin deacetylases were most strongly expressed in the early stages of host invasion, coinciding with spore germination and tissue invasion [57]. Likewise, the rust fungus Uromyces viciae-fabae exhibits massive chitin deacetylase activity when the fungus starts to penetrate through the stomata [58].…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro method was used to produce germinating urediniospores and appressoria to ensure the generation of cDNA libraries with no contaminating plant sequences (Azinheira et al, 2001; Vieira et al, 2012). For the germinating urediniospores sample (gU), 19 mg of spores were spread in sterile distilled water in Petri dishes and incubated for 18 h at 24°C under darkness.…”
Section: Methodsmentioning
confidence: 99%